2010
DOI: 10.1111/j.1349-7006.2010.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4,5‐bisphosphate and PIP5‐kinase Iα are required for invadopodia formation in human breast cancer cells

Abstract: Invadopodia are ventral cell protrusions formed in invasive cancer cells. Because invadopodia have extracellular matrix (ECM) degradation activity, they are thought to function in cancer invasion. In this study, we examined the roles of phosphatidylinositol 4,5-bisphosphate [PI(4,5)P 2 ] and PI(4,5)P 2 -producing enzymes in invadopodia formation in MDA-MB-231 human breast cancer cells. Immunofluorescence analysis showed that PI(4,5)P 2 accumulates at invadopodia on the ventral cell surface. Injection of an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…We recently reported that PI(4,5)P 2 is enriched at invadopodia and blockage of the PI(4,5)P 2 function suppresses invadopodia formation and ECM degradation by invasive human breast cancer cells [39]. We also found that a kinase generating PI(4,5)P 2 , phosphatidylinositol-4-phosphate 5-kinase type Iα (PIPK Iα), accumulates at the invadopodia and that a knockdown of PIPK Iα inhibits invadopodia formation.…”
Section: Phosphoinositide Signaling In Invadopodia Formationmentioning
confidence: 89%
See 1 more Smart Citation
“…We recently reported that PI(4,5)P 2 is enriched at invadopodia and blockage of the PI(4,5)P 2 function suppresses invadopodia formation and ECM degradation by invasive human breast cancer cells [39]. We also found that a kinase generating PI(4,5)P 2 , phosphatidylinositol-4-phosphate 5-kinase type Iα (PIPK Iα), accumulates at the invadopodia and that a knockdown of PIPK Iα inhibits invadopodia formation.…”
Section: Phosphoinositide Signaling In Invadopodia Formationmentioning
confidence: 89%
“…Nck is required for N-WASP-dependent actin polymerization induced by PI(4,5)P 2 and Nck also stimulates PI(4,5)P 2 production via recruitment of PIPK Iα. Considering that Nck and PI(4,5)P 2 are essential for invadopodia formation [9,39], these components may interdependently activate N-WASP to assemble invadopodia structures. Other invadopodia components, such as cofilin and dynamin-2, are also regulated by PI(4,5)P 2 [31].…”
Section: Phosphoinositide Signaling In Invadopodia Formationmentioning
confidence: 99%
“…PtdIns(4,5)P 2 has been shown to surround the invadopodium protrusion and might be generated locally by phosphatidylinositol 4-phosphate 5-kinase type Ia (PIP5KIa) (Yamaguchi et al, 2010). Both PtdIns(4,5)P 2 and PIP5KIa are required for ECM degradation by breast cancer cell invadopodia, but a requirement for invadopodia formation itself was not assessed in that study (Yamaguchi et al, 2010).…”
Section: Regulation By Phosphatidylinositolsmentioning
confidence: 99%
“…PtdIns(4,5)P 2 has been shown to surround the invadopodium protrusion and might be generated locally by phosphatidylinositol 4-phosphate 5-kinase type Ia (PIP5KIa) (Yamaguchi et al, 2010). Both PtdIns(4,5)P 2 and PIP5KIa are required for ECM degradation by breast cancer cell invadopodia, but a requirement for invadopodia formation itself was not assessed in that study (Yamaguchi et al, 2010). Interestingly, the Ras family GTPase ARF6, which activates PIP5KIa downstream of EGF (Honda et al, 1999), localizes to invadopodia and is required for their activity (Hashimoto et al, 2004;Tague et al, 2004).…”
Section: Regulation By Phosphatidylinositolsmentioning
confidence: 99%
“…For the fluorescent gelatin degradation assay, Alexa-Fluor-594-gelatin-coated dishes were prepared as described previously (Yamaguchi et al, 2010). Confocal images were obtained using a confocal laser scanning microscopy (Olympus, FV-1000).…”
Section: Immunofluorescence and Fluorescent Gelatin Degradation Assaymentioning
confidence: 99%